2011
DOI: 10.1002/jcb.23313
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of peptides and proteins into live cells by cell penetrating peptides

Abstract: Internalization of peptides and proteins into live cells is an essential prerequisite for studies on intracellular signal pathways, for treatment of certain microbial diseases and for signal transduction therapy, especially for cancer treatment. Cell penetrating peptides (CPPs) facilitate the transport of cargo-proteins through the cell membrane into live cells. CPPs which allow formation of non-covalent complexes with the cargo are used primarily in this study due to the relatively easy handling procedure. Ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 50 publications
2
62
2
Order By: Relevance
“…Most of these applications use CPPs (Tat, penetratin, polyarginine, VP22) covalently linked to peptides or as fusion proteins (Mussbach et al, 2011;Shin et al, 2014).…”
Section: Application Of Cpps In Medicine and Biotechnologymentioning
confidence: 99%
“…Most of these applications use CPPs (Tat, penetratin, polyarginine, VP22) covalently linked to peptides or as fusion proteins (Mussbach et al, 2011;Shin et al, 2014).…”
Section: Application Of Cpps In Medicine and Biotechnologymentioning
confidence: 99%
“…However, most of the in vivo studies of these and other CPPs were focused on the tissue distributions or bioactivity of CPPs and their cargoes [35,36]. The studies on the intracellular distribution of CPPs in vivo are relatively rare [17,19,37]. Recently, Tsien et al [38,39] have reported the intracellular distribution of D-Arg oligomers in tissue cells, and they claimed that D-Arg oligomers were trapped within endocytic vesicles rather than localized in the cytosol in the cells of organs after injecting mice intravenously (IV) with the maximum tolerated dosage, regardless of whether the CPP was injected alone or attached to a polyanionic domain.…”
Section: Introductionmentioning
confidence: 99%
“…Although several researchers reported the intracellular delivery of proteins by CPPs [33][34][35], the biological activities of the proteins in the cytosol were often indistinct, possibly due to the low efficiency of endosomal escape. Even when intracellular delivery was improved by FPs, previous studies generally revealed the cytosolic localization of cargo proteins [17] but could not reveal their activities, except for some enzymes such as Cre recombinase [16], for which only a small amount is needed to analyze the activity.…”
Section: Discussionmentioning
confidence: 98%